2013
DOI: 10.1371/journal.pone.0069603
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Mental Health Service Has an Impact on Retention in HIV Care: A Nested Case-Control Study in a Japanese HIV Care Facility

Abstract: BackgroundPoor retention in the care of patients with human immunodeficiency virus (HIV) is associated with adverse patient outcomes such as antiretroviral therapy failure and death. Therefore, appropriate case management is required for better patient retention; however, which intervention in case management is important has not been fully investigated. Meanwhile, in Japan, each local government is required to organize mental health services for patients with HIV so that a case manager at an HIV care facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Although it is unknown whether persons diagnosed with mental illness were receiving treatment or other mental health services, psychiatric treatment might be partially responsible for this negative association; receipt of psychiatric medications and ancillary mental health services have been shown to improve retention in care among HIV-infected persons (Cunningham et al, 2007; Lo, MacGovern, & Bradford, 2002; Sherer et al, 2002; Tominari et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether persons diagnosed with mental illness were receiving treatment or other mental health services, psychiatric treatment might be partially responsible for this negative association; receipt of psychiatric medications and ancillary mental health services have been shown to improve retention in care among HIV-infected persons (Cunningham et al, 2007; Lo, MacGovern, & Bradford, 2002; Sherer et al, 2002; Tominari et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Yet mental health is an important determinant of HIV outcomes: among people living with HIV (PLHIV), untreated or poor mental health contributes to late recruitment onto antiretroviral therapy (ART) [ 10 , 11 ], poor adherence to ART [ 12 14 ] and low retention in care [ 15 , 16 ]. Among PLHIV, mental disorders have also been associated with higher rates of HIV disease progression [ 17 , 18 ], hospitalizations [ 19 , 20 ], viralogical failure [ 18 ], and mortality, including suicides [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the studies in this review reported increased retention and adherence to ART among adolescents and young people following the administration of an intervention with psychosocial components [38,39,41,42,45]. Evidence from other studies show that psychosocial interventions comprising of counselling and educational components were effective in increasing adherence to ART among adult patients [57][58][59]. A study evaluating the effects of a psychosocial intervention among PLHIV attending clinical care in Estonia reported that the intervention increased the proportion of patients that were optimally adherent [57].…”
Section: Discussionmentioning
confidence: 84%
“…A study evaluating the effects of a psychosocial intervention among PLHIV attending clinical care in Estonia reported that the intervention increased the proportion of patients that were optimally adherent [57]. Similarly, a study conducted by Tominari et al, [59] reported that the implementation of mental health services demonstrated a signi cant increase in retention in care among PLHIV.…”
Section: Discussionmentioning
confidence: 97%